Cancer and Autoimmune Diseases: A Tale of Two Immunological Opposites? - Elkoshi, Zeev (Frontiers in Immunology, 2022)
The present article compares, side-by-side, cancer and autoimmune diseases in terms of innate and adaptive immune cells involvement, MHC Class I and Class II expression, TGFβ effect, immune modulating drugs effect and the effect of reactive oxygen species. The change in the inflammatory immune reaction during the progress of cancer and the effect of this change on the comorbidity of autoimmune diseases and cancer are discussed. The similar inflammatory properties of autoimmune diseases and early cancer, and the contrasting inflammatory properties of autoimmune diseases and advanced cancer elucidate the increased incidence of many types of cancer in patients with pre-existing autoimmune diseases and the decreased cancer-specific mortality of these patients. Stage-dependent effects of reactive oxygen-species on tumor proliferation are an additional probable cause for these epidemiological observations. The relationship: {standardized incidence ratio (SIR)}>{cancer-specific hazard ratio (HR)} for cancer patients with a history of autoimmune diseases is substantiated and rationalized.